The multisensory body revealed through its cast shadows - Pavani, Francesco; Galfano, Giovanni (Frontiers in Psychology, 2015)
One key issue when conceiving the body as a multisensory object is how the cognitive system integrates visible instances of the self and other bodies with one’s own somatosensory processing, to achieve self-recognition and body ownership. Recent research has strongly suggested that shadows cast by our own body have a special status for cognitive processing, directing attention to the body in a fast and highly specific manner. The aim of the present article is to review the most recent scientific contributions addressing how body shadows affect both sensory/perceptual and attentional processes. The review examines three main points: (1) body shadows as a special window to investigate the construction of multisensory body perception; (2) experimental paradigms and related findings; (3) open questions and future trajectories. The reviewed literature suggests that shadows cast by one’s own body promote binding between personal and extrapersonal space and elicit automatic orienting of attention toward the body-part casting the shadow. Future research should address whether the effects exerted by body shadows are similar to those observed when observers are exposed to other visual instances of their body. The results will further clarify the processes underlying the merging of vision and somatosensation when creating body representations.